2018
DOI: 10.1016/j.neurobiolaging.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and cross-sectional structural magnetic resonance imaging correlates of AV-1451 uptake

Abstract: We examined the relationship between in vivo estimates of tau deposition as measured by F-AV-1451 tau positron emission tomography imaging and cross-sectional cortical thickness, as well as rates of antecedent cortical thinning measured from magnetic resonance imaging in individuals with and without evidence of cerebral amyloid in 63 participants from the Alzheimer's Disease Neuroimaging Initiative study, including 32 cognitively normal individuals (mean age 74 years), 27 patients with mild cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 48 publications
9
76
2
1
Order By: Relevance
“…Meanwhile, the amyloid‐positive AD‐spectrum group showed decreased connectivity, which is consistent with previous studies that MCI/AD in general has often been associated with decreased structural connectivity (Mielke et al, ; Nowrangi et al, ; Wisse et al, ) and atrophy (Das et al, ; Maass et al, ; Xia et al, ). Aβ is hypothesized to increase tau deposition and to accelerate the spread of hyperphosphorylated tau beyond the collateral sulcus into the neocortex, via transsynaptic spread across neural networks.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, the amyloid‐positive AD‐spectrum group showed decreased connectivity, which is consistent with previous studies that MCI/AD in general has often been associated with decreased structural connectivity (Mielke et al, ; Nowrangi et al, ; Wisse et al, ) and atrophy (Das et al, ; Maass et al, ; Xia et al, ). Aβ is hypothesized to increase tau deposition and to accelerate the spread of hyperphosphorylated tau beyond the collateral sulcus into the neocortex, via transsynaptic spread across neural networks.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, patients with a high degree of retention in the entorhinal cortex displayed particularly poor memory functioning (Whitwell et al, 2018). A recent study also links tau burden quantified by [ 18 F]AV-1451 to neurodegeneration, specifically longitudinal brain atrophy (Das et al, 2018). Other neurodegenerative pathology shows unique profiles of tau aggregation as detected by this tracer.…”
Section: Tau Studiesmentioning
confidence: 89%
“…Lower hippocampal volume has also been associated with greater tau radiotracer retention in the hippocampus [8,10]. Longitudinal studies including individuals ranging from CN to demented have further found that higher baseline tau tracer retention is associated with greater rates of brain volume loss [11,12] and global cognitive decline [13–15].…”
Section: Introductionmentioning
confidence: 99%